The Influence of Zakat, Infaq, Sadaqah, and Waqf on Poverty in Aceh Province - Nazar Rianza Maulana; M Rasyidin; M Saleh (SAINTIS Publishing, 2025)
Islamic social finance plays a crucial role in poverty alleviation. This study aims to analyze the impact of Zakat, Infaq, Sadaqah, and Waqf (ZISWAF) management on poverty levels in Aceh Province. Using a quantitative approach, this research processes numerical data and applies statistical analysis to measure the effectiveness of ZISWAF in poverty reduction. The data were obtained from the Aceh Open Data Web documentation covering the period from 2018 to 2024. The findings indicate that effective ZISWAF management can significantly reduce poverty rates. Proper distribution of Zakat, optimization of Infaq and Sadaqah, and productive utilization of Waqf contribute to improving community welfare. However, challenges remain in terms of management transparency, Islamic financial literacy, and coordination between managing institutions and the government. As a recommendation, this study suggests implementing a more structured ZISWAF management system, enhancing Islamic financial literacy in society, and strengthening collaboration between the government and managing institutions to improve the effectiveness of poverty alleviation programs. With the right strategies, ZISWAF can become a more powerful instrument in achieving social welfare in Aceh.